1977
DOI: 10.1126/science.198.4316.519
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vocal Learning in a Sparrow

Abstract: Male swamp sparrows learn their songs; they fail to learn songs of the sympatric song sparrow. Syllables from tape recordings of both species of sparrow were spliced into an array of swamp sparrow-like and song sparrow-like temporal patterns. Swamp sparrows learned only those songs made of swamp sparrow syllables. They did so irrespective of whether the temporal pattern was swamp sparrow-like or song sparrow-like. Selectivity was retained by birds reared in total isolation from adult conspecific sounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
173
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(183 citation statements)
references
References 8 publications
8
173
1
1
Order By: Relevance
“…This requirement is rarely met in song tutoring experiments in sparrows: in most cases, birds are taken as nestlings from the wild. However, in a few studies, offspring taken from the nest as eggs showed learning predispositions (Konishi, 1985;Marler and Peters, 1977). In a particularly compelling case for innate recognition of species-specific vocalizations, brood parasitic brown-headed cowbirds, Molothrus ater, are able to discriminate "chatter" calls of their own species from other heterospecific vocalizations despite being reared by a foster species (Hauber, Russo, & Sherman, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requirement is rarely met in song tutoring experiments in sparrows: in most cases, birds are taken as nestlings from the wild. However, in a few studies, offspring taken from the nest as eggs showed learning predispositions (Konishi, 1985;Marler and Peters, 1977). In a particularly compelling case for innate recognition of species-specific vocalizations, brood parasitic brown-headed cowbirds, Molothrus ater, are able to discriminate "chatter" calls of their own species from other heterospecific vocalizations despite being reared by a foster species (Hauber, Russo, & Sherman, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, naïve individuals may be able to learn from conspecific tutors reliably through predictable patterns of social interactions (Baptista & Petrinovich, 1984). These general mechanisms are not mutually exclusive, and there is experimental evidence for the roles of both song templates and social interactions (Baptista and Petrinovich, 1984;Marler and Peters, 1977). A critical test for the song template model (either innate or acquired very early in life) is to show that young birds are able to discriminate between conspecific and heterospecific songs by the time they begin song memorization.…”
Section: S H I Z U K a I N A N I M A L B E H A V I O U R 9 2 ( 2 mentioning
confidence: 99%
“…To summarize these findings, male swamp sparrows learned only swamp-sparrow syllables regardless of the temporal pattern with which syllables were presented (Marler & Peters, 1977). For male song sparrows, both temporal and phonological patterns were important (peters, Searcy, & Marler, 1980).…”
mentioning
confidence: 92%
“…When children learn a particular feature of their language, did the data of experience allow for the construction of knowledge through general cognitive mechanisms of categorization and generalization, or did that experience play more of a triggering role, facilitating the expression of abstract core knowledge in a way that is consistent with the speech of the ambient community? In other areas of biology, this kind of tension is often resolved experimentally through selective rearing (1)(2)(3). Restricting the exposure of the learning organism to only a subset of the data that a normally developing organism receives allows us to identify the role of data in typical development.…”
mentioning
confidence: 99%